ESSZone resorts encouraged to install own radars - Roslan, Fiqah (Borneo Post (KK), 2016)
KOTA KINABALU: Negative perception by the public on security in the State will not affect Eastern Sabah Security Command (ESSCom) operations, and are instead more of a burden to society itself.